2020
DOI: 10.5114/kitp.2020.94190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-opioid anesthesia in cardiac surgery on dynamics of pro-inflammatory interleukin-6

Abstract: Introduction With coronary artery bypass grafting, patients are subjected to additional risk caused by both surgical treatment itself and pathophysiological changes in homeostasis, provoked by the action of anesthetics and cardiopulmonary bypass. Material and methods The study involved 60 patients, who had been subjected to coronary artery bypass grafting with cardiopulmonary bypass. All patients were divided into two groups: group I (30 patients) – low-opioid scheme of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Due to the importance of IL-6 levels in the development of early cardiac complications, a possible mechanism for reducing their frequency in low-opioid anesthesia is a reduction of the inflammatory response, which could be achieved by direct opioid dose reduction and the addition of lidocaine, ketamine or dexmedetomidine. This hypothesis is confirmed by our previous study, in which low-opioid anesthesia was characterized by significantly lower levels of IL-6 after CPB compared to standard doses of opioids [10].…”
Section: Discussionsupporting
confidence: 86%
“…Due to the importance of IL-6 levels in the development of early cardiac complications, a possible mechanism for reducing their frequency in low-opioid anesthesia is a reduction of the inflammatory response, which could be achieved by direct opioid dose reduction and the addition of lidocaine, ketamine or dexmedetomidine. This hypothesis is confirmed by our previous study, in which low-opioid anesthesia was characterized by significantly lower levels of IL-6 after CPB compared to standard doses of opioids [10].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown the clinical relevance of the IL-6 and other interleukins, since they can be useful as predictive factors that can identify patients at risk for postoperative complications [30]. Furthermore, Il-6 has been described as a good predictor of morbidity and mortality [31], cardiac complications and shorter duration of mechanical ventilation [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, serum levels of this cytokine have shown a positive correlation with the time of surgery (r = 0.554, p < 0.01) and the amount of blood lost during surgery (r = 0.427, p < 0.01) since IL-6 is an important mediator in response to trauma [16]. Previous studies have shown that IL-6 and other interleukins can be useful as predictive factors that can identify patients at risk for postoperative complications [30], since it has been described as a good predictor of further morbidity and mortality [31], cardiac complications and shorter duration of mechanical ventilation [32].…”
Section: Discussionmentioning
confidence: 99%